Essentials of stochastic processes - Durrett, Richard, 1951- (New York : Springer, 1999)
"This book is for a first course on stochastic processes to be taken by undergraduates or masters students who have had a course in probability theory, but who have not had a course in measure theory. It covers Markov chains in discrete and continuous time, Poisson processes, renewal theory, and Brownian motion and martingales. The last two topics are important for the brief treatment of option pricing."--BOOK JACKET.
"The book presents only the essentials of the subject, the parts of the theory most important for applications. To allow readers to choose their own level of detail, many of the proofs begin with a nonrigorous answer to the question "Why is this true?" followed by a proof that fills in the missing details."--BOOK JACKET.
Review of Probability -- 1. Markov Chains -- 2. Martingales -- 3. Poisson Processes -- 4. Continuous-Time Markov Chains -- 5. Renewal Theory -- 6. Brownian Motion.
Includes bibliographical references and index.
Keywords: Stochastic processes